Unregistered artesian Well Management in Pasuruan, Indonesia: An Attempt to Protect Groundwater Resources - Heru Hendrayana; Indra Agus Riyanto; Azmin Nuha; Ahmad Rif’an Khoirul Lisan (Faculty of Geography, Universitas Gadjah Mada, 2021)
The number of unregistered artesian wells increases every year in the northern slopes of Bromo Volcano, Pasuruan. Artesian wells are used for domestic needs and agricultural irrigation but are not followed by environmentally sound groundwater use. The purpose of this study is to assess the potential for groundwater, groundwater use, wasted groundwater, and recommendations for groundwater management. The groundwater potential was obtained by measuring the depth of the groundwater table, piezometric surface of artesian wells, and geoelectrical data. Water uses were obtained from calculations based on the Indonesian National Standard. The amount of wasted groundwater was obtained by comparing the groundwater potentials, groundwater uses, and groundwater discharges from unregistered artesian wells. Water transfer was assessed by selecting unregistered artesian wells with discharges able to fulfill the water demands of each village. Groundwater in the Sub-Districts of Gondang Wetan and Winongan has high potential consisting of 1 unconfined aquifer group and two confined aquifer groups. Gondang Wetan and Winongan Sub-Districts are characterized as wasting groundwater potential through unregistered artesian wells. The discharge flow of unregistered artesian wells exceeds the water needs (>100%) in Winongan and Gondang Wetan Sub-Districts. Groundwater can be managed by water transfer, closure of artesian wells, and regulation of artesian wells use. Water can be transferred to areas not covered by Artesian wells in 20 villages. The number of artesian wells used for water transfer is 20 with a discharge of 5-20 liters/s.